The secretarial ghetto: Myth or reality? : a study of secretarial work in England, France and Germany - Truss, Catherine J.G. [Verfasser] (My University, 1993)
"This paper reports the findings of a study on secretarial work in England, France and Germany, which aimed to discover whether secretarial work can justly be described as a female 'ghetto' occupation. Questionnaires were issued to secretaries working in matched management consultancy and publishing firms in the three countries; 185 questionnaires were received and 61 interviews were carried out with bosses, secretaries and personnel representatives. It was found that promotion out of secretarial work is extremely rare, which corroborates the 'ghetto' thesis. However, secretarial job content, especially in France and Germany, was found to be wide- ranging and varied, which runs counter to that thesis. Overall, conflicting evidence was found across the three countries, which suggests that women's work is not necessarily constructed in the same way in different countries, and points to the role played by national institutions in shaping patterns and experiences of women's employment." (author's abstract, IAB-Doku) ((en)) Im Rahmen eines internationalen Vergleichs wird der Frage nachgegangen, ob es sich bei Sekretariatsarbeiten um ein weibliches "Ghetto" handelt. In Hinblick auf die geringen beruflichen Veränderungsmöglichkeiten der dort tätigen Frauen wird diese Annahme bestätigt. Im Vergleich zwischen England, Frankreich und Grossbritannien zeigt sich jedoch auch, wie sich unterschiedliche institutionelle Bedingungen jeweils auf Frauenarbeit auswirken. (IAB)
Das Ghetto der Sekretärinnen: Mythos oder Wirklichkeit? Eine Studie über die Arbeit von Sekretärinnen in England, Frankreich, Deutschland
Keywords: S 6.4.3.5 Bürofach-, Bürohilfskräfte; G 2.3.1 Arbeitsteilung & -organisation; G 2.4.1 Bildungs- und Berufswege; G 2.4.4 Biografiegestaltung; G 1.2.4.2.5 Grundstücks- und Wohnungswesen, unternehmensbezogene Dienstleistungen; G 1.2.4.2 Dienstleistung; G 1.3.3.3 Mobilität; P 1.3 Frauen; Sekretärin; Frauenberuf; Internationaler Vergleich; Berufsproblem; Arbeitszufriedenheit; Beruflicher Aufstieg; Unternehmensberatung; Verlag; Berufliche Mobilität; Frauen in Einzelberufen; Frauenarbeit